Light without heat : the observational mood from Bacon to Milton - Simon, David Carroll (Cornell University Press, 2018)
"Argues for the importance of states of careless inattention and easygoing dispassion to literary and scientific works inspired by Francis Bacon's philosophy of nature, retrieving a counternarrative to the rise of scientific method and its attendant ethos of rigor in the intellectual culture of seventeenth-century England"--